Evaluation of a school-based digital literacy corridor program using the CIPP Model - Ardi, Arditama; Siswantoyo, Siswantoyo; Setiawan, Risky; Septiana, Yolandaru; Safitri, Rina (Graduate School, Universitas Negeri Yogyakarta, 2025)
This study aims to evaluate the effectiveness of the Digital Literacy Corridor Program at SMP Negeri 1 Simpang Renggiang by applying the CIPP (Context, Input, Process, Product) evaluation model. The approach used in this study is descriptive quantitative. The research subjects consisted of 144 students at SMP Negeri 1 Simpang Renggiang. Data were collected through a Likert scale questionnaire and direct observation, then analyzed descriptively using average value calculations and the Respondent Achievement Level (TPR). The results showed that in the context dimension, the suitability of the program's objectives with the students' digital literacy needs was effective, with an average value of 3.57 and a TPR of 89.17%. In the input dimension, the availability and utilization of supporting resources were categorized as quite effective with an average score of 3.17 and an RAT of 79.17%, where there were still obstacles in terms of internet network stability and digital content variation. In terms of input, the availability and utilization of supporting resources were categorized as quite effective, with an average score of 3.17 and a TPR of 79.17%, although there were still obstacles in terms of internet network stability and digital content variation. In terms of process, the implementation of the Digital Literacy Corridor Program is categorized as quite effective, although teacher involvement in providing guidance and motivation to students has not yet reached an optimal level. Furthermore, in terms of product, the program has had a positive impact on increasing student learning independence and digital literacy competencies, with an average score of 3.37 and a TPR of 84.17%, which is categorized as effective. Based on these findings, it can be concluded that the Digital Literacy Corridor Program at SMP Negeri 1 Simpang Renggiang has been implemented effectively and has made a positive contribution to the development of students' digital literacy. However, improvements in the quality of supporting resources and strengthening the role of teachers are needed to ensure that the program can be implemented optimally and sustainably.